Process design for green hydrogen production. (4th March 2020) - Mosca, Lorena; Medrano Jimenez, Jose Antonio; Wassie, Solomon Assefa; Gallucci, Fausto; Palo, Emma; Colozzi, Michele; Taraschi, Stefania; Galdieri, Giulio
Abstract: A membrane assisted process for green hydrogen production from a bioethanol derived feedstock is here developed and evaluated, starting from the conventional Steam Methane Reforming (SMR) process. Such a process is suitable for centralized hydrogen production, and is here analyzed for a large-scale H2 production unit with the capacity of 40.000 Nm 3 /h. The basic Steam Ethanol Reforming (SER) process scheme is modified in a membrane assisted process by integrating the Pd-membrane separation steps in the most suitable reaction steps. The membrane assisted process, configured in three alternative architectures (Open architecture, Membrane Reactor and Hybrid architecture) was evaluated in terms of efficiencies and hydrogen yields, obtaining a clear indication of improved process performance. The alternative membrane assisted process architectures are compared to the basic SER process and to the benchmark SMR process fed by natural gas, for an overall comparative assessment of the efficiency and specific CO2 emissions and for an economic analysis based on the operating expenditures. Highlights: Investigation of large-scale green hydrogen production by bioethanol. Membrane assisted process for green hydrogen production. Comparative process performance and economics.